Persepsi Murid Terhadap Amali Pertanian Dalam Kemahiran Hidup Bersepadu - Mohamad Ismail, Suhada (1998)
The purpose of this study is to describe students’ perception toward practical work carried out in agricultural section of Living Skills subject. A questionnaire was administered to collect data from students regarding their perceptions and responses towards the implementation of the practical work carried out in the agricultural section. The reliability of the instrument is 70.8%. A total of 226 Form Three students took part as respondents in the study and the response rate was 100%. Data was analysed by SPSSPC+. Inferential and descriptive statistics were used in the analysis. The result showed that student agreed the practical works do benefit them and they showed positive responses towards the teaching activities carried out. The result also revealed that there were still not enough facilities in school for this practical work to be carried out effectively. The practical work was supposed to be have been carried out when the respondents were in Form One but until then many practical topics have not yet been covered. The result also showed that there were no significant differences between the student attitude toward the practical work and their family background. There were gender differences showed in the academic achievements for this subject between boys and girls. The boys tend to be better than girls and boys showed a more positive attitude towards the practical works.